Pesquisa de arbovírus : dengue, Zika, Chikungunya e febre amarela em leite humano e estudo de série de casos em gestantes suspeitas de infecção por Zika vírus, Cuiabá-MT - Uecker, Marli Eliane (2021)
Arbovirus circulation has raised concerns about the possibility of transmission through breastfeeding. Objective: Identify the available scientific evidence on the possible transmission of dengue, Zika, Chikungunya and yellow fever viruses through breast milk. To characterize human milk donors, the factors that motivated them to donate and analyze the prevalence of dengue arboviruses, Zika, Chikungunya and yellow fever in samples of human milk donated to the Human Milk Bank (HMB) and describe cases of pregnant women suspected of infection by Zika virus (ZIKV), Cuiabá-MT. Method: Systematic review was based out on the recommendations of the Preferred Reporting Items for Systematic Reviews and recorded in the International Prospective Register of Systematic; descriptive and qualitative cross-sectional study with donors from HMB of Cuiabá-MT, October/2018 to August/2019 and a cross-sectional study of case series of pregnant women suspected of being infected with ZIKV, December/2017 to August/2019 admitted to the Hospital Geral (HG) or Hospital Universitário Júlio Müller (HUJM). The tests performed for the detection of arboviruses were real-time polymerase chain reaction (RTPCR for four arboviruses) and IgM and IgG immunoenzymatic tests for ZIKV. Descriptive statistics, Z test of proportion and chi-square were performed with a 5% significance level. Thematic analysis was used for qualitative questions. Results: Twelve cases in 11 publications related to arbovirus transmission through breastfeeding remained in the systematic review. In 6/12 cases, there was a report of temporary interruption of breastfeeding. Only for ZIKV, positive infectivity tests were found with breast milk. In the donor/HMB profile (N=324), the following prevailed: adults (86.73%), non-white (76.23%), with a partner (74.38%), with complete or incomplete higher education (52.78%), with paid work (60.19%), home with up to 4 people (68.52%), prenatal care in the public service (58.95%), complete prenatal care (87.96%), gestation at term (73.15%), cesarean delivery (54.63%), multiparous (51.23%) and without health problems (82.10%). Non-white donors performed prenatal care mainly in the public service. There was a significant association between donors with higher and incomplete education with prenatal care in the private network/health insurance (64.33%) and term pregnancy (79.53%). Adolescent (N=39/316) and adult (277/316) donors showed a significant increase in “low weight”, a significant decrease in “eutrophic”; and in adults there was also a significant increase in “obesity”. They learned about HMB through the media (N=95/324) and the motivation (N=53/324) was of an altruistic or supportive nature and excess milk production. The results of milk samples from 324 donors were all negative (RT-PCR and ZIKV IgG). The 16 pregnant women suspected of having ZIKV infection were on average 23.6 years old, none of their newborns (NB) had microcephaly, all RT-PCR and ZIKV IgM were negative. The frequency of maternal ZIKV IgG was 18.7% and 12.5% in newborns. Conclusions: The evidence corroborated for temporary interruption only for suspicion of wild yellow fever or after vaccination of the nursing mother for yellow fever. Donors with complete or incomplete higher education had favorable conditions for the donation of breast milk. Donors' nutritional assessment indicates the need for public policies to improve nutritional care during prenatal care. The media demonstrated influence on the knowledge of the HMB and the altruistic or solidary nature and excess milk production were the main reasons for donation. The arboviruses studied were not present in the donated milk. Among pregnant women suspected of being infected with the Zika virus, there was no case of recent viremia. The presence of ZIKV IgG antibodies in newborns probably reflects the transplacental passage of maternal antibodies.